Endoscopic two-port technique for orbital tumours: combined transnasal and sublabial approach - Matoušek, Petr; Masárová, Michaela; Lubojacký, Jakub; Kopecký, Adam; Němčanský, Jan; Misiorzová, Eva; Krejčí, Tomáš; Komínek, Pavel; Lipina, Radim (Neurologia i Neurochirurgia Polska, 2022)
INTRODUCTION: The aim of this study was to present the indications for a combined endoscopic transnasal and sublabial transantral approach for the surgical treatment of orbital lesions. MATERIAL AND METHODS: This case study enrolled 10 patients scheduled for endoscopic transnasal surgery for treating orbital lesions from 2009 to 2020. When the tumour was localised to the medial part of the orbit, patients underwent endoscopy with a transnasal mononostril approach. Alternatively, when the tumour was localised to the mediocaudal part of the orbit, and when instrument manoeuvreability was limited, the transnasal approach was combined with a sublabial transantral approach. Herein, we evaluate the indications, complications, and advantages of monoportal and combined two-portal approaches. RESULTS: 8/10 patients (80%) underwent surgery with the transnasal mononostril approach, and 2/10 (20%) underwent surgery with the combined transnasal mononostril and sublabial transantral approach. In the two latter cases, visualisation of the operation field was excellent, and there was adequate room for manipulating instruments. CONCLUSIONS: The combined mononostril-transantral approach provided the space necessary to manoeuvre instruments and to visualise the surgical field in treating mediocaudal orbital lesions. CLINICAL IMPLICATIONS: This two-portal approach enables extensive resections of intraconal lesions. It should be considered to be a suitable and safer alternative to the binostril approach.
Keywords: Endoscopy; endoskopie; lidé; nádory orbity; Orbital Neoplasms; Humans